Role of muscarinic receptors in the contraction of jejunal smooth muscle in the horse: An in vitro study. (December 2017) - Menozzi, Alessandro; Pozzoli, Cristina; Poli, Enzo; Bontempi, Giada; Serventi, Paolo; Meucci, Valentina; Intorre, Luigi; Bertini, Simone
Abstract: Nonselective antimuscarinic drugs are clinically useful in several pathologic conditions of horses, but, blocking all muscarinic receptor (MR) subtypes, may cause several side effects. The availability of selective antimuscarinic drugs could improve therapeutic efficacy and safety. We aimed to enlighten the role of different MR subtypes by evaluating the effects of nonselective, and selective M1, M2 and M3 MR antagonists on the contractions of horse jejunum. Segments of circular muscle of equine jejunum, were put into organ baths, connected to isotonic transducers, and the effects on ACh concentration-response curves, and on electrical field stimulation (EFS)-evoked contractions of intestinal preparations, induced by nonselective or selective MR antagonists, compared to pre-drug level, were studied. Atropine (nonselective MR antagonist), pirenzepine (selective M1 antagonist), and p-FHHSiD (selective M3 antagonist) competitively antagonized ACh (pA2  = 9.78 ± 0.21; 7.14 ± 0.25 and 7.56 ± 0.17, respectively). Methoctramine (selective M2 antagonist) antagonized ACh in a concentration-unrelated fashion; however, it competitively antagonized carbachol, a nonselective muscarinic agonist (pA2  = 6.42 ± 0.23). Atropine dose-dependently reduced EFS-evoked contractions, reaching a maximal effect of − 45.64 ± 6.54%; the simultaneous block of neurokinin receptors, almost completely abolished the atropine-insensitive contractions. p-FHHSiD dose-dependently reduced EFS-induced contractions, while pirenzepine caused a minor decrease. Methoctramine, ineffective up to 10 − 7  M, enhanced the contractions at 10 − 6  M; the block of neurokinin receptors abolished the increase of contraction. Cholinergic contractions of horse jejunum are mainly mediated by M3 receptors; M2 selective antagonists seem to scarcely affect cholinergic, and to enhance neurokininergic contractions of equine jejunum, thus their use entails a lower risk of causing intestinal hypomotility, compared to nonselective drugs. Highlights: The role of muscarinic receptors in horse jejunum motility was investigated in vitro. The effects of nonselective and selective M1, M2 and M3 antagonists were assessed. Drug-induced modifications of ACh- and EFS-evoked contractions were evaluated. Cholinergic contraction of horse jejunum is mediated by M3 receptors. M2 receptors have an inhibitory activity on contractions of neurokininergic nature.